Low risk of apparent transmission of vancomycin-resistant Enterococci from bacteraemic patients to hospitalized contacts - Mutters, Nico T.; Brooke, Russell John; Frank, Uwe; Heeg, Klaus (American journal of infection control, 2013)
Background - Vancomycin-resistant enterococci (VRE) are primarily opportunistic pathogens with incalculable clinical significance. In addition, the effectiveness of isolation in VRE is often not easily assessed. The goals of this study were to estimate the transmissibility of VRE of patients with VRE bacteraemia to other hospitalized patients and to document reliable epidemiologic data on all VRE cases in a large health care center. - Methods - A prospective survey on in-patients colonized and/or systemically infected with VRE was conducted at a 2,000-bed tertiary care university hospital in Germany. All roommates of VRE bacteraemia patients were analyzed. Pulsed-field gel electrophoresis was performed to assess clonal relatedness. - Results - 16,507 Screening tests were performed on 9,258 patients, of which 560 tested positive for VRE (6.1%). Nineteen patients also suffered from VRE bacteraemia, an incidence of 3.4%. This cohort was multimorbid and had high rates of exposure to external risk factors (eg, previous hospital stay prior to admission, 78.9%). The transmission rate to contacts was low (3.5%). Contact time of negative contacts was significantly lower than that of VRE-positive contacts (19.3 hours vs 72.0 hours, respectively, P < .006). - Conclusion - VRE bacteraemia was found exclusively in multimorbid patients, transmission occurred seldom, and average contact time of positive contacts was very high. The risk of transmission of VRE from bacteraemic patients to hospitalized contacts is low.
Gesehen am 16.11.2021